Diglosia Bahasa Adat dalam Bahasa Meto pada Masyarakat Multietnik Biboki Anleu - Mauk, Vincentius; Sau, Palmerya (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
The aim of this study is to explore diglossia in the effort to preserve the indigenous language within the Meto language through a sociolinguistic approach. The focus of the research is on diglossia and the preservation of unique words, phrases, language styles, and sacred words in the takanab speech during funeral ceremonies in the multiethnic community of Biboki Anleu. The indigenous language in the Meto language has a rich historical and cultural significance. This is demonstrated by the consistent use of takanab speech at funeral ceremonies. The preservation of the high variety of the indigenous language shows that the Biboki Anleu community continues to maintain the speech, utilizing unique words, phrases, language styles, and sacred words. Although the use of informal or slang language is common in everyday communication, takanab speech is still employed in formal or sacred situations (such as funeral ceremonies). The communication style of the indigenous language within the Meto language also has its own unique features that support social interaction and reinforce cultural identity.